2010
DOI: 10.1002/mrm.22244
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative magnetization transfer and myelin water imaging of the evolution of acute multiple sclerosis lesions

Abstract: Quantitative magnetization transfer imaging provides in vivo estimates of liquid and semisolid constituents of tissue, while estimates of the liquid subpopulations, including myelin water, can be obtained from multicomponent T 2 analysis. Both methods have been suggested to provide improved myelin specificity compared to conventional MRI. The goal of this study was to investigate the sensitivity of each technique to the progression of acute, gadolinium-enhancing regions of multiple sclerosis. Magnetization tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
116
2
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(132 citation statements)
references
References 48 publications
12
116
2
2
Order By: Relevance
“…Over time, T2 decreases to that of chronic lesions (84,139,170), similar to the behaviour of T1. One study detected monoexponential relaxation in acute WM lesions, which became bi-exponential during remission, and finally returned to mono-exponential as the lesion turned into a chronic lesion (168).…”
Section: Qmri In Mssupporting
confidence: 62%
See 3 more Smart Citations
“…Over time, T2 decreases to that of chronic lesions (84,139,170), similar to the behaviour of T1. One study detected monoexponential relaxation in acute WM lesions, which became bi-exponential during remission, and finally returned to mono-exponential as the lesion turned into a chronic lesion (168).…”
Section: Qmri In Mssupporting
confidence: 62%
“…The initial increase in T2 of the lesion has also been attributed to increased water content due to the oedema (84,168). Over time, T2 decreases to that of chronic lesions (84,139,170), similar to the behaviour of T1.…”
Section: Qmri In Msmentioning
confidence: 69%
See 2 more Smart Citations
“…[16,92] Previous reports of relaxation measurements in MS lesions have shown variable result. Some findings are in line with our study, with shorter T2 in enhancing lesions and longer T2 in non-enhancing lesions [93], and longer T2 in enhancing lesions compared to NAWM [94]. An early study reported a decrease in T1 and T2 over time in acute brain stem lesions.…”
Section: Paper IIsupporting
confidence: 92%